A Blockchain-Based Personal Health Record System for Emergency Situation. (8th October 2022) - Liu, Yuan; Du, Yan; Zhang, Yanan; Li, Yuan; Cyril, Leung; Miao, Chunyan; Tan, Qingfeng; Tian, Zhihong
Abstract : A personal health record (PHR) system stores personal health-related information, which can assist physicians in quickly forming appropriate treatment plans in emergency situations. Because a PHR contains lots of sensitive information, the patients are only willing to share their records with authorized doctors with their permission. There are three main challenging issues: (1) it is costly to store and maintain the growing PHRs data; (2) the existing PHR systems still face the privacy leakage risk during data transmission and access control processes; and (3) the response speed cannot meet the need in an emergency situation, especially when the patients are unconscious. In this paper, based on the permissioned blockchain Hyperledger Fabric, we propose a PHR management system preserving patients' privacy and also supporting emergency access. In the system, we use reencryption technology and the anonymous identity mapping mechanism to protect patient privacy and use smart contracts to define access control strategies in an emergency situation. Furthermore, we use a quick response code and bloom filter to optimize system performance. The security analysis and experimental results show that our proposed framework guarantees the privacy of patient data from multiple aspects while improving the efficiency with which doctors can obtain PHR information.